2020
DOI: 10.1186/s13063-019-3986-z
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture treatment on the motor area of the scalp for motor dysfunction in children with cerebral palsy: study protocol for a multicenter randomized controlled trial

Abstract: BackgroundScalp acupuncture has been widely used as treatment for motor dysfunction in children with cerebral palsy in China. Previous studies have failed to provide high-quality evidence to demonstrate the effectiveness of this treatment in children with cerebral palsy. No high-quality randomized controlled trials on scalp acupuncture have been published. The aim of this study is to evaluate the effectiveness of Jiao’s scalp acupuncture when combined with routine rehabilitation treatment versus routine rehabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…[ 8 ] Clinical studies claim that acupuncture can effectively treat children with cerebral palsy [ 9 ] and restore brain function. [ 10 ] Acupuncture is simple, safe and effective, with few adverse reactions, and has great advantages in clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Clinical studies claim that acupuncture can effectively treat children with cerebral palsy [ 9 ] and restore brain function. [ 10 ] Acupuncture is simple, safe and effective, with few adverse reactions, and has great advantages in clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown increased microcirculatory blood flow and decreased blood flow resistance after acupuncture treatment through transcranial doppler ultrasound (Hsiu, Hsu, Chen, Hsu, & Lin, 2013). Also, acupuncture might be involved in influencing the metabolic activity of neurons, promoting cerebral remodeling and plasticity, and regulating the glucose metabolism in poststroke patients (Wang, Shi, et al, 2020;. Acupuncture could affect the function of the brain and muscles through cortical excitability and motor cortex functional changes in poststroke patients (Sun et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous epidemiological studies have shown that the incidence of stroke increased every year in urban China (Feigin, Lawes, Bennett, Barker-Collo, & Parag, 2009;Wang, 2015). For example, the prevalence rate of stroke increased from 0.57% in 1986 to approximately 2.13% in 2013, in China (Wang, Shi, et al, 2020;. Many stroke patients can suffer from different types of sequelae (Wang, Shi, et al, 2020; such as cognitive decline and motor dysfunction, which can affect their quality of life (QOL), as well as can be a burden for the family and society (Levine et al, 2015;Lo Coco, Lopez, & Corrao, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, acupuncture at Zusanli, Hegu, and Chize on both sides and Quchi, Kongzui, Lieque can significantly improve children’s pneumonia; 40 acupuncture at Ququan, Quchi, Zhongwan, Qihai, Zusanli and Sanyinjiao can improve the gastrointestinal symptoms of patients with Crohn’s disease, such as chronic dyspepsia, reflux, abdominal pain and excessive diarrhea; 41 acupuncture of Fengchi, Zusanli and other acupoints can significantly improve children’s enuresis, 42 and acupuncture at four Shengong and Baihui can significantly improve central nervous system diseases, such as cerebral palsy in children. 43 For childhood autism, common acupuncture methods include brain tri-points, four-spirit points, spirit setting points, mental tri-points, spirit waiting-up points and foot mental points, etc. 44 Acupuncture can also significantly improve the symptoms of various animal models, such as animal model of COPD, 45 animal model of cerebra hemorrhage, 46 animal model of PCOS 47 and animal model of ASD.…”
Section: Discussionmentioning
confidence: 99%